Bromide Dose in Dogs With Epilepsy Living Close to Coastal Areas and Living More Inland: A Retrospective Observational Study - Lichtenauer, Esther A.; Evers, Bas; van den Broek, Jan; Mandigers, Paul J. J. (Frontiers in Veterinary Science, 2022)
Potassium bromide is a frequently used antiseizure medication with a half-life time of over 25 days. Oral intake of sodium chloride as well as renal function influence this half-life time and may have an influence on the needed dose to get proper serum levels. The hypothesis is that dogs living close to coastal areas require a greater potassium bromide dose than dogs living more inland. The main study objective was to determine the relationship between bromide dose, serum bromide concentration, treatment duration, type of food, concurrent therapies and the proximity of the dog’s residency to a coastal area. A retrospective cross-sectional study was performed. A total of 658 bromide serum measurements were retrieved from the veterinary faculty's laboratory archive, Utrecht University, The Netherlands. Information on the bromide dose, renal function, treatment period, type of food, concurrent therapies and residence was obtained retrospectively from owners of all dogs using a postal survey. A dataset of 220 unique study units was created. The dogs were grouped based on their residence (proximity to the coast > or < 50km). Differences between the groups of dogs regarding bromide dose, serum bromide concentration, treatment duration, type of food and concurrent therapies were analyzed to evaluate the effect of residence on bromide dose and serum concentration. Results: Although not statistically significant there is a trend that dogs living in close proximity to the sea may require a higher dose of potassium bromide to maintain therapeutic concentrations compared to dogs living more inlands. Additional studies are needed to further explore this observation.